Mineralogical and Geochemical Response to Fluid Infiltration into Cambrian Orthopyroxene-Bearing Granitoids and Gneisses, Dronning Maud Land, Antarctica - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Taubald, Heinrich; Elvevold, Synnøve (Minerals, 2024)
Fluid infiltration into Proterozoic and Early Palaeozoic dry, orthopyroxene-bearing granitoids and gneisses in Dronning Maud Land, Antarctica, has caused changes to rock appearance, mineralogy, and rock chemistry. The main mineralogical changes are the replacement of orthopyroxene by hornblende and biotite, ilmenite by titanite, and various changes in feldspar structure and composition. Geochemically, these processes resulted in general gains of Si, mostly of Al, and marginally of K and Na but losses of Fe, Mg, Ti, Ca, and P. The isotopic oxygen composition (δ18OSMOW = 6.0‰–9.9‰) is in accordance with that of the magmatic precursor, both for the host rock and infiltrating fluid. U-Pb isotopes in zircon of the altered and unaltered syenite to quartz-monzonite indicate a primary crystallization age of 520.2 ± 1.0 Ma, while titanite defines alteration at 485.5 ± 1.4 Ma. Two sets of gneiss samples yield a Rb-Sr age of 517 ± 6 Ma and a Sm-Nd age of 536 ± 23 Ma. The initial Sr and Nd isotopic ratios suggest derivation of the gneisses from a relatively juvenile source but with a very strong metasomatic effect that introduced radiogenic Sr into the system. The granitoid data indicate instead a derivation from Mid-Proterozoic crust, probably with additions of mantle components.
Keywords: Dronning Maud Land; NARE 1996/97; geokjemi; geokronologi; geologi; mineralogi

A local geoid in Dronning Maud Land - The NARE 96/97 Geoid - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola (IGeS Bulletin, 2001)
The main purpose of the present paper is to estimate the orthometric height of the Global Positioning System (GPS)-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m above sea level Troll has been connected to the Geodetic Infrastructure forAntarctica (GIANT)-network, but it’s orthometric height remains undetermined. A local geoid has been determined based on gravity-, tidal- and GPS-observations and available gravity anomalies. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta andTroll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE 1996/97; Troll forskningsstasjon; geodesi; kartlegging